(untitled) (Nigerian Journal of Technology, 2018)
ABSTRACT This paper presents the use of non-conventional, renewable (sustainable) and locally available material in the form of vegetable fibre sourced from palm oil tree (Male Inflorescence of Oil Palm Ash; MIPA) for expansive soil improvement. Expansive soil subgrade of Imo – Clay Shale formation traversing Amuro – Okigwe section of Owerri – Okigwe road were identified for its intermittent flexible pavement failure. Samples of this subgrade were mixed with MIPA at varying proportions in line with the Scheffe’s model approach to improve the natural engineering properties of the soil. Hence, MIPA – Amuro subgrade stabilization models for the maximum dry density (MDD) and California bearing ratio (CBR) were developed. These models showed good correlations with the experimental results in the control tests, as they possess less than 3% differences. For 5% significance value, α, and 2 degrees of freedom; the t – value obtained from the standard statistical table, is 5.78. This value is greater than the t – values obtained in the experimental and model results of the control experiment. Similarly, the F– value obtained from the standard statistical table, is 19.00. This value is greater than the F – value obtained between the experimental results and model results in an independent control experiment for CBR response. It is slightly differed for MDD response towards the right extremum. The deviation is however minor, as the left extremum condition is very satisfactory. Hence, the slight inconsistency allowed, having satisfied by the Student’s t - Test. The inverse of this statistical F – value is 0.0526, which is also smaller than any of the F – value obtained. Based on statistical significance level, the Null hypothesis is accepted. Hence, the model is adequate. In the CBR results, 10.5% MIPA content in the soil gives the greatest strength (CBR value) of 8.13KN, which is about 31% increase in strength from 6.21KN of natural CBR. When MIPA content in the modified soil is in excess (about or greater than 11%), the CBR value of modified soil begins to reduce. Keywords: Mixture Design, Simplex Lattice, Amuro – Okigwe, Subgrade, MIPA, Scheffe’s Model http://dx.doi.org/10.4314/njt.v38i1.9